Changes in Functional Outcomes in People with High-Energy Ankle Trauma After the Use of the ReAktiv Posterior Dynamic Element™ Orthosis and a Rehabilitation Program: A Case Series - Gardner, Sarah; Frecklington, Mike; Rose, Kirsten; Carroll, Matthew (Lippincott, Williams & Wilkins, 2023)
The aim of this study was to examine lower-limb function in 2 patients that received a ReAktiv Posterior Dynamic Element™ (PDE) orthosis and 6-week rehabilitation program after a high-energy trauma injury to the lower limb. Lower-limb function was assessed using the lower extremity functional score, walking performance through the 2-minute walk test, and dynamic mobility and balance through the single-leg balance, timed stair ascent, and the 4-square step test. A 6-week physiotherapy-led rehabilitation program was also implemented. Data showed improvements in lower extremity function, walking performance, mobility, and balance measures after 8 weeks of wearing the ReAktiv PDE™ orthosis and completion of the rehabilitation program. The ReAktiv PDE™ orthosis combined with a lower-limb rehabilitation program shows potential as a treatment option to improve lower-limb function and walking performance and return sufferers of high-energy trauma injury to functional levels seen in healthy cohorts.
Keywords: 0903 Biomedical Engineering; 1106 Human Movement and Sports Sciences; Rehabilitation; 3202 Clinical sciences; 4201 Allied health and rehabilitation science; 4207 Sports science and exercise